Magnetic resonance imaging based 3D models of left ventricular wall thickness and dyssynchrony in acute myocardial infarction / Amirah Khalid - Amirah, Khalid (2018)
Acute Myocardial Infarction (AMI) is a leading cause of cardiac dysfunction affecting over half a million people worldwide annually. Existing clinical diagnostic and assessment methods could be improved to facilitate early detection and personalized treatment of AMI with the ultimate goal to reduce the associated morbidity and mortality. A 3D personalized LV modelling and thickening assessment framework was developed in this research for assessing regional wall thickening dysfunction and dyssynchrony in AMI patients. A total of 44 subjects consisting of 29 AMI patients and 15 healthy subjects were recruited. Steady-state free precession cine MRI scans were performed for all subjects, and LGE MRI scans were additionally performed for AMI patients. The quantitative spatial thickening measurements across all cardiac phases were computed and correlated against clinical evaluation of infarct transmurality by experienced cardiac radiologist based on AHA 17-segment model and summarized for each individual patient as thickening index (TI) in mm and dyssynchrony index (DI) in % R-R interval. Non-parametric 2-k related sample-based Kruskal-Wallis test was performed to identify significance in thickening and time-to-peak measurements between non-infarcted segments and infarcted segments. Mann-Whitney U test was used to assess TI and DI significance between healthy subjects and AMI patients. The results showed that healthy LV wall segments undergo significant wall thickening (p<0.05) during ejection and have on average thicker wall (8.73±1.01 mm) compared with infarcted wall segments (2.86±1.11 mm). Myocardium with thick infarct (i.e. >50% transmurality) underwent remarkable wall thinning during contraction (TI = 1.46±0.26 mm) as opposed to healthy myocardium (TI = 4.01±1.04 mm). For AMI patients, LV which shows sign of thinning were found to be associated with significantly higher percentage of dyssynchrony as compared to healthy subjects (DI = 15.0 ± 5.0% vs. 7.5±2.0%, p<0.01). Also, strong correlation was found between TI and left ventricular ejection fraction (LVEF) (r=0.892, P<0.01), and moderate correlation between DI and LVEF (r=0.494, P<0.01). The regional wall thickening and dyssynchrony indices extracted from the proposed framework have shown to highly correlate with infarct severity, therefore suggestive of possible practical clinical utility.